Pengembangan Media Pembelajaran Matematika Berbasis Video Animasi Materi Bangun Ruang Kelas V SDN Gunung Sahari Utara 01 Pagi - Fitri, Annisa; Amelia, Winda (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to produce mathematics learning media based on animation of spatial building materials for fifth grade elementary school students, to determine the development of mathematics learning media based on animation of geometric materials, and to determine the effectiveness of mathematics learning media based on animation of geometric materials. This development research uses the Dick and Carrey development model which consists of 10 stages. The results of this study show that: (1) has produced mathematics learning media based on animated video of spatial material, (2) the product has been validated by several experts, namely: design experts, material experts, learning experts, language experts by getting value results 84.75% with a very valid and effective category for use by fifth grade elementary school students, (3) product trials on 6 students got 88% results with a very valid and effective category used by fifth grade elementary school students, (4) test the use of the product with 32 students also got a value of 88.43% with a very valid and effective category for use by students in the learning process and can increase student learning interest.